Pengaruh Penggunaan Media Pembelajaran Digital Terhadap - Aliftia Putri Rahmadian; Angraini Faomasi Zebua; Annisa Nur Rahma (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
The development of digital technology has brought significant changes in the field of education, particularly in the use of innovative learning media to enhance students' learning motivation. This study aims to analyze the influence of using digital learning media on students' learning motivation based on a review of various previous research findings. The method used is a literature review (library research) with a descriptive-qualitative approach, analyzing scientific journal articles published between 2020 and 2026. The results of the review indicate that various types of digital learning media such as Quizizz, Wordwall, interactive videos, mobile learning, e-learning, and web learning have consistently been proven effective in increasing students' learning motivation across different levels of education. Factors affecting their effectiveness include teachers' digital competence, attractive and user-friendly media design, and ease of access to devices and the internet, as well as support from the school environment. The positive impact is not only limited to short-term motivation enhancement but also contributes to the development of learning independence, critical thinking skills, creativity, and student readiness to face the Industrial Revolution 4.0 and Society 5.0 era. This study concludes that the integration of digital learning media is an effective strategy to increase student learning motivation, but its success highly depends on teacher competence, media design quality, and the availability of equitable access for all students. Recommendations from this study include the need for continuous teacher training, provision of adequate technological infrastructure, and inclusive education policies to address the digital access gap